Focus and impact on gender equality, youth, and social inclusion - CGIAR Initiative on NEXUS Gains (International Water Management Institute, 2024)
A NEXUS Gains impact area brief shares how the Initiative uses people-centered approaches to prioritize the well-being and strategic interests of women, youth, and marginalized groups across the water–energy–food–ecosystems nexus.